Branched Actin Maintains Acetylated Microtubule Network in the Early Secretory Pathway - Azumi Yoshimura; Stéphanie Miserey-Lenkei; Evelyne Coudrier; Bruno Goud (Cells, 2021)
In the early secretory pathway, the delivery of anterograde cargoes from the endoplasmic reticulum (ER) exit sites (ERES) to the Golgi apparatus is a multi-step transport process occurring via the ER-Golgi intermediate compartment (IC, also called ERGIC). While the role microtubules in ER-to-Golgi transport has been well established, how the actin cytoskeleton contributes to this process remains poorly understood. Here, we report that Arp2/3 inhibition affects the network of acetylated microtubules around the Golgi and induces the accumulation of unusually long RAB1/GM130-positive carriers around the centrosome. These long carriers are less prone to reach the Golgi apparatus, and arrival of anterograde cargoes to the Golgi is decreased upon Arp2/3 inhibition. Our data suggest that Arp2/3-dependent actin polymerization maintains a stable network of acetylated microtubules, which ensures efficient cargo trafficking at the late stage of ER to Golgi transport.